1998
DOI: 10.1016/s1010-7940(98)00143-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications after bronchoplastic procedures in the treatment of bronchial malignancies1

Abstract: Bronchoplastic procedures represent a fairly safe therapy opportunity in patients with centrally localized bronchial carcinoma and compromised or uncompromised pulmonary function. In this study the complication rate was higher after sleeve resection of the bronchus as compared with wedge resection. Pleural coverage of the anastomosis was not effective to prevent major complications due to dehiscence of the bronchial anastomosis. A pedicled muscle flap could be a valuable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 10 publications
0
17
0
5
Order By: Relevance
“…22 It is due to sputum retention secondary to edema at the anastomosis and mucociliary dysfunction related to mucosal interruption and denervation of the reimplanted lobe(s). It occurs more often after sleeve resection of the lower lobes (where anastomotic kinking is potentially the greatest) and less often after sleeve resection of the upper lobes (where the distal bronchial lumen is made wider to meet the size of the proximal lumen).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…22 It is due to sputum retention secondary to edema at the anastomosis and mucociliary dysfunction related to mucosal interruption and denervation of the reimplanted lobe(s). It occurs more often after sleeve resection of the lower lobes (where anastomotic kinking is potentially the greatest) and less often after sleeve resection of the upper lobes (where the distal bronchial lumen is made wider to meet the size of the proximal lumen).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…22 This complication can generally be avoided if one applies the surgical principles involved during construction of a healthy anastomosis, including avoidance of nodal overdissection and unnecessary devascularization, careful approximation of the bronchial ends, and most importantly wrapping the anastomosis with a pedicled intercostal fl ap if the anastomosis is considered to be at risk of dehiscence. 23 The operative mortality associated with bronchoplasties should be <5% ( Table 1).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Park et al reported that the incidence of bronchial stenosis and the rate of BPF were 2.6 and 1.5 , respectively in 191 patients who underwent wedge bronchoplastic 4 . In another comparative study of sleeve lobectomy and wedge lobectomy, wedge lobectomy has been reported as a useful bronchoplastic procedure in terms of safety, prognosis, and postoperative respiratory function [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic site is covered with pericardial fat, parietal pleura, internal intercostal muscle or fibrin glue to prevent leak and fistula [11]. Sleeve lobectomy has been reported to have higher rates of anastomotic complications, similar tumor and nodal clearance and similar local recurrence [5-24 %] and operation mortality [2.7-7.5 %] when compared to wedge bronchoplasty [12][13][14]. Postoperative sputum retention has been reported to be as high as 14.7 % after wedge bronchoplasty and often requires bronchoscopic toileting [14].…”
Section: Discussionmentioning
confidence: 99%